Formulation optimization of the powder for suspension of flixweed seeds (Descurainia sophia L.), a Persian medicinal drink - Hesari Zahra; Ebrahimi-Najafabadi Heshmatollah; Beheshti-Kisomi Sanaz; Naseri Maryam; Parvinroo Shirin (Vojnosanitetski Pregled)
Background/Aim. Flixweed (Descurainia sophia L.) beverage has been used in Persian medicine as an effective remedy for constipation. Allyl isothiocyanate (AITC), the main ingredient of flixweed essential oil, has been claimed to regulate gastrointestinal contractility. The aim of the study was to stabilize the flixweed beverage, enhance its flavor, and determine the AITC content in the flixweed seeds (FS). Methods. To prepare a stable formulation of flixweed with desirable organoleptic properties, the optimal amount of tragacanth as a stabilizer, stevia as a sweetener, and lime and cinnamon powders as flavoring agents were mixed with flixweed solution. The shelf lives of the suspensions at room temperature (25 ºC) and refrigerator temperature (5 ºC) were evaluated. The viscosity and pH of the suspensions were also investigated. Finally, flixweed essential oil was obtained using the Clevenger apparatus. The amount of AITC in FS essential oil was determined by gas chromatography coupled with mass spectroscopy (GC-MS). Results. Based on our findings, two formulas, including FS (5 g), stevia (3 g), cinnamon (300 mg) or lime (400 mg), and 100 mL of water, had the optimum textural and organoleptic properties. Furthermore, adding 0.5% tragacanth gum as a suspending agent was able to stabilize the FS beverage. From 200 g of FS, 0.14 mL of essential oil was extracted, which corresponded to 0.07% (v/w). GC-MS analysis revealed that each 100 g of FS contained 24.85 mg of AITC, equating to 0.025% w/w AITC. Conclusion. Due to the presence of AITC in FS and the favorable characteristics of the FS suspension, this formulation, in the form of a sachet, can be suggested as an herbal supplement product for industrial production.